Utilization of Obstetric Analgesia for Labor Pain Management and Associated Factors among Obstetric Care Providers in Public Hospitals of Addis Ababa, Ethiopia: A Cross-Sectional Study - Rediet Gido; Tesfaye Assebe Yadeta; Abera Kenay Tura (Obstetrics and Gynecology International)
Background. In low-income countries, pain-free labor initiative is an emerging concept and still parturient undergoes through painful labor; this is not different in Ethiopia; despite the national direction to use analgesia for labor pain and strong demand from the women, evidence on utilization of obstetric analgesia for labor pain management in Ethiopia is scarce. The objective of this study was to assess level of obstetric analgesia utilization and associated factors among obstetric care providers in public hospitals in Addis Ababa, Ethiopia. Methods. An institution-based cross-sectional study was used. All obstetric care providers working in labor and delivery units in public hospitals in Addis Ababa were included. The data were collected using a self-administered structured questionnaire. After checking for completeness, data were entered into Epi-data 3.1 and analyzed using SPSS 20. Bivariate and multivariable logistic regressions were used to identify factors associated with utilization of obstetric analgesia. Result. Of 391 obstetric care providers included in the study, 143 (36.6%; 95% CI: 31.5–40.9%) reported providing labor analgesia. Having adequate knowledge (AOR 2.7; 95% CI: 1.37–5.23), ten and more years of work experience (AOR 4.3; 95% CI: 1.81–10.13), and availability of analgesics (AOR 3.3; 95% CI: 1.99–5.53) were significantly associated with providing labor analgesia. Conclusion. Slightly more than 3 in 10 obstetric care providers reported providing labor analgesics to women. Training of providers and ensuring adequate supply of analgesics is required to make sure that women in labor would not suffer from labor pain.